ChemInform Abstract: Iodoetherification of Isosorbide‐Derived Glycals: Access to a Variety of O‐Alkyl or O‐Aryl Isosorbide Derivatives. Issue 35 (8th August 2013) - Berini, Christophe; Lavergne, Aurelie; Molinier, Valerie; Capet, Frederic; Deniau, Eric; Aubry, Jean‐Marie
Abstract This method gives access to substituted isosorbide derivatives which can be further functionalized.